ACUTE TOXICITY AND RELAXANT ACTIVITY OF TOTAL FLAVONOIDS OF FORSSKAOLEA TENACISSIMA. : JPUMHS;2024:14:04,60-70 .http://doi.org/10.46536/jpumhs/2024/14.04.561 - Shamaila Zahid1, Afrasiab Amir2, Falak Naz3, Amber Javaid4, Waqas Zahid5, Safia Bibi6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
BACKGROUND: Abdominal spasms have historically been treated with the whole plant of Forsskaolea tenacissima. Thus, the study’s goals were to identify the safe dosage range, identify the mechanism or mechanisms behind Forsskaolea tenacissima’s therapeutic usage for gastrointestinal spasms, and extract the plant’s total flavonoids. METHODS: Forsskaolea tenacissima’s total flavonoids were examined for potential antispasmodic efficacy in isolated rabbit jejunal preparations after an acute toxicity research was conducted to establish the safe dosage range prior to in vivo tests. RESULTS: With comparable EC50 values of 4.22 ± 0.849 mg/ml and 0.607 ± 0.0306 mg/ml, total flavonoids from Forsskaolea tenacissima decreased both spontaneous and high K+-induced contractions in isolated rabbit jejunal preparations. The concentrations used were 0.01, 0.03, 0.1, 0.3, 1.0, 3.0, 5.0, and 10.0 mg/ml. The mechanism was verified by constructing a calcium curve in the decalcified rabbit jejunal preparation with and without verapamil 0.1, 0.3 µm. The EC50 value of the total flavonoids in Forsskaolea tenacissima is -2.55 ± 0.00 at 0.1 mg/ml, whereas the control has an EC50 value of -2.80 ± 0.00. In the presence and absence of 0.1 µM verapamil, the corresponding EC50 Log Ca++ M values are 1.71 ± 0.07 and -2.45 ± 0.00, respectively. This suggests that the total flavonoids of Forsskaolea tenacissima follow voltage-gated calcium channels for calcium influx since the right shift of Verapamil and the test sample’s total flavonoids right shifts are comparable. CONCLUSION: According to the study, Forsskaolea tenacissima’s total flavonoids have antispasmodic action that may be mediated via voltage-gated Ca++ channel blockage, and the safe dose is 100 mg/kg. This gives the plant a solid pharmacological foundation for its potential medical application in treating intestinal spasm.